A case report on and chronic calcific pancreatitis primary systemic amyloidosis with symptomatic gastric involvement - Kumar, Rajesh; Chakraborthy, SR; A., Bandopadhyay; Pandit, VK; Bandi, HK (International Journal of Medical Research and Review, 2016)
Systemic amyloidosis is a disorder characterized by extracellular deposition ofamyloid in various organs and tissues including the gastrointestinal tract, kidney, heart, and liver. Gastric involvement occurs in 8–12% of patientswith only 1% being symptomatic. Histological involvement of gastrointestinal tract baring stomach is common but is often subclinical. Moreover pancreatic involvement is also rare. Herein we report a case of a 37-year old lady patient who presented with macroglossia, periorbital purpura, abdominal symptoms and on evaluation wasdiagnosedto be having systemic amyloidosis involving stomach and chronic calcific pancreatitis.